Development of E-plantbook Learning Resources based on Mobile Learning Applications with a Scientific Approach - Maila Shofa Maghfiroh; Enni Suwarsi Rahayu; Talitha Widiatningrum (International Conference on Science, Education, and Technology, 2022)
Abstract. The development of mobile learning application-based e-plantbook with a scientific approach is one of the efforts to improve the quality of an ideal learning resource for Plantae material in Senior High School. This study aims to develop mobile learning application-based e-plantbook with a scientific approach for Plantae material that was tested to measure the level of validity and practicality at SMA Negeri 1 Kembang, Jepara Regency, Central Java Province. This study used the Research and Development (R and D) method by S. Thiagarajani, Dorothy and Melvyn I. The results of the development were tested for validity by material experts and media experts, and tested for practicality by teachers and students. The results of validation by material experts was obtained 83% with very valid criteria, while the results of validation by media experts was obtained 95.6% with very valid criteria. The results of the validity of the e-plantbook were then tested for practicality by the teacher and 20 students which were obtained 91% and 82% with very good criteria. These results indicate that the e-plantbook is proven to be valid and practical as a source of student learning in SMA/MA.